2013
DOI: 10.1186/2228-5326-3-30
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and optical properties of zinc oxide nanoparticles

Abstract: Zinc oxide nanoparticles were synthesized using a simple precipitation method with zinc sulfate and sodium hydroxide as starting materials. The synthesized sample was calcined at different temperatures for 2 h. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and proton-induced X-ray emission (PIXE) analysis. SEM images show various morphological changes of ZnO obtained by the above method. The average crystallite sizes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
193
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(224 citation statements)
references
References 32 publications
12
193
0
3
Order By: Relevance
“…01-079-5604). The estimated crystal size using Scherer's equation was 25 nm; the obtained results were in accordance with the previously published literatures [17,23]. …”
Section: Preparation and Characterization Of Zonpssupporting
confidence: 80%
“…01-079-5604). The estimated crystal size using Scherer's equation was 25 nm; the obtained results were in accordance with the previously published literatures [17,23]. …”
Section: Preparation and Characterization Of Zonpssupporting
confidence: 80%
“…Platinum peaks were detected in both spectra, which could be due to the platinum coating made at the time of characterization. Kumar et al [18] also reported that EDS study of ZnO samples by method II had pure ZnO phases. From EDS spectra, it was revealed that ZnO nanoparticles synthesized by method II were highly pure, more than that from method I. TEM study: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The images show that the synthesized nanoparticles are homogenous, uniformly distributed over the surface. Kumar et al [18] reported different morphologies obtained for the ZnO samples calcined at three different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Intensive studies have been done on various factors, such as precursor concentrations [8,9], temperature [10,11], duration [12], surfactant concentration [7], dopant concentration [6], solvent medium [13], pH of reaction mixture [14] and source of light during synthesis [15], which individually and collectively affect the shape, size and optical properties of ZnO. Various researchers [16][17][18] suggested that NaOH concentration plays a vital role in determining the morphology, size and optical bandgap of obtained nanostructures.…”
Section: Introductionmentioning
confidence: 99%